Influence of joint interface on mechanical properties in dissimilar friction welds. Issue 1 (2nd January 2022) - Cheepu, Muralimohan; Cheepu, Harinadh; A, Karpagaraj; Che, Woo Seong
ABSTRACT: The solid-state joining process of friction welding became an interesting option as it provides sound welds without cracks compared to the conventional arc welding techniques. The joining of dissimilar materials is not feasible using arc welding methods due to the difference in their physical properties. Friction welding allows the successful joining between dissimilar materials with excellent mechanical and metallurgical properties. In this study, the dissimilar joint of austenitic stainless steel to high tensile alloy steel was welded using friction welding. The interface microstructure, axial shortening, joint temperature, microhardness and tensile strength of the welds were evaluated. The thickness of the intermixing zone was identified at an interface and its variation with the welding parameters. The effect of intermixing zone in dissimilar welds and its effect on the mechanical properties was investigated. The thickness of the intermixing zone is proportional to the tensile strength of the welds. The microhardness profiles were recorded that the highest hardness obtained at the intermixing zone and dynamically recrystallised zone. Temperature of the joint interface was influenced by the thickness of the intermixing zone and the axial shortening of the substrates at the mating surfaces.